Stilmittel bei Afrahat dem persischen Weisen - Haefeli, Leo (Syriac Studies Library, 2010)
Drawing on the more progressed fields of Greek and Roman and Arabic rhetoric, Haefeli here presents Aphrahat's style in terms of numerous stylistic categories. Naturally, the work is brimming with examples (in Syriac and German) from Aphrahat